Uncovering Essential Tremor Genetics: The Promise of Long-Read Sequencing - Marsili, Luca; Duque, Kevin R.; Bode, Rachel L.; Kauffman, Marcelo A.; Espay, Alberto J. (Frontiers in Neurology, 2022)
Long-read sequencing (LRS) technologies have been recently introduced to overcome intrinsic limitations of widely-used next-generation sequencing (NGS) technologies, namely the sequencing limited to short-read fragments (150–300 base pairs). Since its introduction, LRS has permitted many successes in unraveling hidden mutational mechanisms. One area in clinical neurology in need of rethinking as it applies to genetic mechanisms is essential tremor (ET). This disorder, among the most common in neurology, is a syndrome often exhibiting an autosomal dominant pattern of inheritance whose large phenotypic spectrum suggest a multitude of genetic etiologies. Exome sequencing has revealed the genetic etiology only in rare ET families (FUS, SORT1, SCN4A, NOS3, KCNS2, HAPLN4/BRAL2, and USP46). We hypothesize that a reason for this shortcoming may be non-classical genetic mechanism(s) underpinning ET, among them trinucleotide, tetranucleotide, or pentanucleotide repeat disorders. In support of this hypothesis, trinucleotide (e.g., NOTCH2NLC) and pentanucleotide repeat disorders (e.g., ATTTC repeats) have been revealed as pathogenic in patients with a past history of what has come to be referred to as “ET plus”, bilateral hand tremor associated with epilepsy and/or leukoencephalopathy. A systematic review of LRS in neurodegenerative disorders showed that 10 of the 22 (45%) genetic etiologies ascertained by LRS include tremor in their phenotypic spectrum, suggesting that future clinical applications of LRS for tremor disorders may uncover genetic subtypes of familial ET that have eluded NGS, particularly those with associated leukoencephalopathy or family history of epilepsy. LRS provides a pathway for potentially uncovering novel genes and genetic mechanisms, helping narrow the large proportion of “idiopathic” ET.